2022
DOI: 10.1039/d2nr03445j
|View full text |Cite
|
Sign up to set email alerts
|

Control of triboelectrification on Al–metal surfaces through microstructural design

Abstract: Micro/nano-AAO was fabricated on the surface of Al, and the short-circuit current was reduced 8.77 times through microstructure and composition regulation. Besides, a positive correlation between the contact area and the charge density was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Aluminum (Al) alloys are widely utilized in aerospace, automotive, marine, and other industries due to the excellent properties in low density, high thermal conductivity, and ease of processing and forming. Despite the natural formation of protective oxide films on this material surface, its thin thickness (typically only several nanometers) , usually makes it a severe challenge to withstand corrosive attacks, especially under extreme conditions. Therefore, some techniques including organic coating, , electroplating, and anodizing , have been developed to reduce this risk.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum (Al) alloys are widely utilized in aerospace, automotive, marine, and other industries due to the excellent properties in low density, high thermal conductivity, and ease of processing and forming. Despite the natural formation of protective oxide films on this material surface, its thin thickness (typically only several nanometers) , usually makes it a severe challenge to withstand corrosive attacks, especially under extreme conditions. Therefore, some techniques including organic coating, , electroplating, and anodizing , have been developed to reduce this risk.…”
Section: Introductionmentioning
confidence: 99%
“…They found that all of the output performance of TENG with nanostructured PDMS is better than TENG with flat PDMS. The maximum voltage of the TENG with the cicada wing reached 210 V. 25 To date, a variety of methods to fabricate the micro/nanostructures have been reported, including lithography, 26 anodic aluminum oxide (AAO), 27,28 nanoimprinting, 29 etching, 30 and self-assembly. 31 Different methods to fabricate nanostructures have pros and cons of being suitable for various application scenarios.…”
Section: Introductionmentioning
confidence: 99%